High‐Power Multimode Random Fiber Laser for Speckle‐Free Imaging. Issue 12 (5th November 2021) - Wang, Shanshan; Zhang, Weili; Yang, Ning; Ma, Rui; Zhang, Yanli; Wang, Zhao; Zhang, Jinchuan; Rao, Yunjiang
Abstract: New light sources with low spatial coherence and high brightness are crucial for high‐quality imaging. In this paper, such a light source is reported, which is formed by combining random lasing used as seed light with a multimode fiber (MMF) mediated master oscillator power amplifier (MOPA) for power scaling and spatial decoherence. Experimental results show that the proposed multimode random fiber laser (MM‐RFL), with low noise, high spectral density, and high power efficiency, can achieve a maximum output power of 100.6 W and speckle contrast of as low as 0.037. Furthermore, MM‐RFL‐based speckle‐free imaging is demonstrated. The imaging quality can be improved by increasing the output power of the MM‐RFL as its spatial coherence decreases with an increasing number of effective modes excited in the MMF. Such a MM‐RFL provides a powerful light source for speckle‐free imaging applications where high power and low spatial coherence are essential for high‐quality imaging. Abstract : A high‐power multimode random fiber laser with high spectral density and high efficiency is demonstrated for speckle‐free imaging, which can achieve a maximum output power of 100.6 W and speckle contrast of 0.037. The quality of speckle‐free imaging is improved by increasing the power of the laser as its spatial coherence decreases with increasing excited modes in the multimode fiber.